Wolf-Hirschhorn Syndrome with Hyperparathyroidism: A Case Report and a Narrative Review of the Literature - Xia, Changqing; Kumar, Dibyendu; You, Bei; Streck, Deanna L.; Osborne, Lisa; Dermody, James; Jiang, Jie-Gen; Pletcher, Beth A. (Journal of Pediatric Genetics, 2021)
Wolf-Hirschhorn syndrome (WHS) is a contiguous gene deletion condition. The WHS core phenotype includes developmental delays, intellectual disabilities, seizures, and distinctive facial features. Various other comorbidities have also been reported, such as hearing loss, heart defects, as well as eye problems and kidney problems. In this report, we present a case of WHS accompanied by hyperparathyroidism and hypercalcemia, which has not been previously reported. A girl was born at 37 weeks of gestation by vaginal delivery. She was small for the gestational age (2,045 g) and admitted to neonatal intensive care unit. She had typical WHS facial features and was found to have bilateral small kidneys associated with transient metabolic acidosis and renal insufficiency. She had right-sided sensorineural hearing loss, a small atrial septal defect, and colpocephaly and hypoplasia of corpus callosum. She had a single seizure which was well controlled with an oral antiepileptic medication. Cytogenetic studies demonstrated a large terminal chromosome 4p deletion (21.4 Mb) and 4p duplication (2.1 Mb) adjacent to the deletion. A unique finding in this patient is her consistently elevated levels of parathyroid hormone and serum calcium, suggesting hyperparathyroidism. We present this rare case along with a review of the literature and hope to draw an attention to a potential relationship between WHS and hyperparathyroidism.
Keywords: Wolf-Hirschhorn syndrome; 4p deletion; 4p duplication; hyperparathyroidism